LPS-induced CXCR4-dependent migratory properties and a mesenchymal-like phenotype of colorectal cancer cells. Issue 1 (2nd January 2017) - Liu, Wen-Ting; Jing, Ying-Ying; Yan, Fei; Han, Zhi-Peng; Lai, Fo-Bao; Zeng, Jian-Xing; Yu, Guo-Feng; Fan, Qing-Min; Li, Rong; Zhao, Qiu-Dong; Wu, Meng-Chao; Wei, Li-Xin
ABSTRACT: Colorectal cancer (CRC) is the most commonly diagnosed cancer worldwide, and over 50% of patients will develop hepatic metastasis during the course of their disease. CXCR4 and its ligand, stromal cell-derived factor 1α (SDF-1α)/chemokine (C-X-C motif) ligand 12 (CXCL12) have been revealed as regulatory molecules involved in the spreading and progression of a variety of tumors. Here we have shown that lipopolysaccharides (LPS) promoted the migratory capacity of colon cancer cells in vivo and in vitro, which correlated with the activation of SDF-1α/CXCR4 axis and epithelial-mesenchymal transition (EMT) occurrence. Additionally, we found that LPS-induced CXCR4 expression and EMT through NF-κB signaling pathway activation. And inhibition of NF-κB pathway, which recovered the epithelial phenotype and attenuated CXCR4 expression, inhibited cell migratory capacity. Clinically, high levels of CXCR4 always correlated with metastasis and poor prognosis of CRC patients. In conclusion, LPS participate in the whole process of hepatic metastasis of CRC, not only causing liver damage resulting in the production of SDF-1α, but also enhancing the invasive potential of CRC cells by promoting CXCR4 expression and EMT occurrence, which would contribute to the enhancement of cell migration and invasion.